2019
DOI: 10.1093/europace/euz160
|View full text |Cite
|
Sign up to set email alerts
|

Micra pacemaker implant after cardiac implantable electronic device extraction: feasibility and long-term outcomes

Abstract: Aims We aimed at investigating the feasibility and outcome of Micra implant in patients who have previously undergone transvenous lead extraction (TLE), in comparison to naïve patients implanted with the same device. Methods and results Eighty-three patients (65 males, 78.31%; 77.27 ± 9.96 years) underwent Micra implant at our centre. The entire cohort was divided between ‘post-extraction’ (Group 1) and naïve patients (Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Likewise, feasibility and electrical performance of M-TPS in a patients population previously undergone to a transvenous lead extraction (TLE) procedure has clearly been discussed [15]. All data suggested that technical complexity of the implant procedure was similar in both patient groups, those underwent TLE and those who received M-TPS has first pacing option, in terms of fluoroscopy time and number of device deployments.…”
Section: Leadless Pacing: Safety Firstmentioning
confidence: 99%
“…Likewise, feasibility and electrical performance of M-TPS in a patients population previously undergone to a transvenous lead extraction (TLE) procedure has clearly been discussed [15]. All data suggested that technical complexity of the implant procedure was similar in both patient groups, those underwent TLE and those who received M-TPS has first pacing option, in terms of fluoroscopy time and number of device deployments.…”
Section: Leadless Pacing: Safety Firstmentioning
confidence: 99%
“…In addition, device encapsulation might be protective against bacterial infiltration. The parylene coating of the Micra TPS might also play a role in reducing bacterial adherence 21 . Finally, the turbulent blood flow at the site of Micra TPS might reduce the opportunity of bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that in patients receiving Micra following extraction due to a device infection, no recurring infections occured in longterm follow-up. [33][34][35]…”
Section: Discussionmentioning
confidence: 99%